A writer's handbook for engineers - McMurrey, David A. (Thomson, 2008)
This handbook covers numerous types of common writing projects likely to be found in a career as an engineering student or a practicing engineer. Support is given in document-development efforts by a useful variety of tools to plan, develop, format and finalize engineering writing projects. Plenty of examples from engineering fields and disciplines are given, specializing the content to engineering students while still covering the basic mechanics of writing with a wide range of writing-related topics.